2017
DOI: 10.7324/jabb.2017.50503
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Production of Polyhydroxyalkanoates (PHAs) from Glycerol by Zobellella taiwanensis Azu-IN1

Abstract: Polyhydroxyalkalonates (PHAs) are biodegradable thermoplastics that are receiving immense attention as an alternative to petroleum derived plastics. The present study aimed to produce PHA using cheap and ecofriendly biodiesel waste glycerol as a substrate. Several PHA-producing bacterial isolates were isolated from different environmental samples and their efficacy for PHA production was assessed. Isolate Azu-IN1 showed the highest PHA production and was identified as Zobellella taiwanensis Azu-IN1 using 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Citrate utilization medium was prepared (Abdel-Rahman et al, 2017). It contained (g/L): NaCl, 5.0; MgSO4.7H2O, 0.2; (NH4).…”
Section: Biochemical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrate utilization medium was prepared (Abdel-Rahman et al, 2017). It contained (g/L): NaCl, 5.0; MgSO4.7H2O, 0.2; (NH4).…”
Section: Biochemical Testsmentioning
confidence: 99%
“…Accordingly, 1.5 g/L was considered the optimal concentration for PHA production. Different researchers reported that ammonium chloride is the preferable source of nitrogen in PHA production (Aramvash et al, 2015;Abdel-Rahman et al, 2017;and El-Metwally et al, 2020). Briefly, 1.0 g/L ammonium chloride causes the maximum PHA production (0.95 g/L) and PHA content (20.96%, w/w).…”
Section: Impact Of Ammonium Chloride Concentrationmentioning
confidence: 99%